Cardioprotective study of Eriobotrya japonica leaf extracts against carbon tetrachloride induced toxicity in rats - Abdelaaty A. Shahat; Riaz Ullah; Ali S. Alqahtani; Omer I. Fantoukh (Elsevier, 2023)
The Rosaceae family includes the evergreen subtropical tree known as Eriobotrya japonica Lindl (loquat). To test the effect of several E. japonica leaf extracts on shielding the heart from carbon tetrachloride (CCl4) cytotoxic effects, we employed carbon tetrachloride (CCl4), a highly toxic chemical, to cause cardiotoxicity in rats. The heart function enzymes that were examined were lactate dehydrogenase (LDH) and Creatine Kinase. When compared to both the hazardous and normal groups, it was discovered that the protective dose of ethyl acetate extract (200 mg/Kg) and aqueous extract (100 and 200 mg/Kg) lowered the cardiac indicators. Total protein, malondialdehyde (MDA), and non-protein sulfhydryls (NP-SH) indicators were used to assess myocardial oxidative stress. Rats pretreated with ethyl acetate (200 mg/Kg) and aqueous extract (100 and 200 mg/Kg) showed higher levels of total protein than the control group. When compared to the silymarin group, all of the loquat leaf extracts examined in this study increased the amount of the MDA enzyme. The data also demonstrated that, when compared to the results from the normal group, aqueous extract (100 and 200 mg/Kg) enhanced the amount of NP-SH. The histopathology showed that administration of all loquat leaf extracts at doses of (100 mg/kg, 200 mg/kg) before CCl4 intoxication greatly reduced the modifications that were exhibited by CCl4 and preserved cardiac muscles that were very equivalent to those of normal control. Based on the aforementioned data, we deduced that loquat leaf aqueous extract provided the highest protection for heart tissue against the effects of CCl4 intoxication. Through chemical examination of the methanolic extract, four flavonoids were extracted and identified. Their structures were found to be kaempferol-3-O-rhamnoside 1, quercetin-3-O-rhamnoside 2, quercetin-3,7 di-O-glycerides 3, and roseoside 4.